2023
DOI: 10.1186/s12885-023-11106-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia inhibits cellular function and induces immunogenic cell death in renal cell carcinoma

Yin Huaqi,
Dong Bingqi,
Zhao Yanhui
et al.

Abstract: Background In recent years, hyperthermia has been widely applied as a novel strategy for cancer treatment due to its multiple antitumour effects. In particular, the potential influences of hyperthermia on the tumour immune microenvironment may improve the efficacy of immunotherapies. However, the effect of hyperthermia on renal cell carcinoma (RCC) has not been well characterized until now. Methods In the present study, we primarily evaluated the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mild-hyperthermia therapy is a therapeutic approach that utilizes mild heat to enhance the permeability of tumor blood vessels and expand the pores of tumor microvessels, thereby facilitating improved penetration of therapeutic drugs and minimizing damage to surrounding normal tissues. 27–30 Clinical evidence has consistently demonstrated that combining hyperthermia with chemotherapy effectively enhances local tumor control rates and prolongs patient survival. 31 Xia et al synthesized photo-responsive gold nanoparticles (AuNPs), which exhibited laser-induced accumulation towards the tumor and generated photothermal effects at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…Mild-hyperthermia therapy is a therapeutic approach that utilizes mild heat to enhance the permeability of tumor blood vessels and expand the pores of tumor microvessels, thereby facilitating improved penetration of therapeutic drugs and minimizing damage to surrounding normal tissues. 27–30 Clinical evidence has consistently demonstrated that combining hyperthermia with chemotherapy effectively enhances local tumor control rates and prolongs patient survival. 31 Xia et al synthesized photo-responsive gold nanoparticles (AuNPs), which exhibited laser-induced accumulation towards the tumor and generated photothermal effects at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Due to the deviation from the optimal temperature, the efficiency of many organelles and sub‐organelles is weakened. 10 Inhibition of certain transmembrane proteins disrupts ion transport, causing intracellular accumulation of Ca 2+ , which leads to endoplasmic reticulum stress and caspase‐dependent apoptosis. 11 Secondly, from an immunological perspective, hyperthermia significantly enhances anti‐tumour immune responses, encompassing both specific and non‐specific immunity.…”
Section: Introductionmentioning
confidence: 99%